Manejo da adubação nitrogenada no milho com diferentes plantas de inverno, sob plantio direto - Coutinho-Neto, André Mendes [UNESP]; Coutinho, Edson Luiz Mendes [UNESP]; Orioli Júnior, Valdeci; Corá, José Eduardo [UNESP]; Silva, Alysson Roberto Baizi; Scatolin, Marcelo [UNESP] (My University, 2013)
The nitrogen (N) utilization by maize grown in a no-tillage system is dependent on the quality of the preceding crop residues, which may promote differences in N fertilization efficiency with respect to time. Thus, the purpose of this study was to evaluate the nutritional state, dry matter production and grain yield of maize grown in a clayey soil (Typic Acrustox) under a no-tillage system. The split-plot experimental design was set up in randomized complete blocks with three replications, in which the main plot was treated with different N application strategies and the split-plots were planted with winter crops (soybean and maize). The fertilizer strategies (rate: 120 kg ha-1 of N) used were as follows: (0 - 0), (20 - 100), (60 - 60), (120 - 0) and (0 - 120), with the first number corresponding to the rate of N (kg ha-1) applied before planting and the second number corresponding to the top dressing rate (V4-5 stage). Nitrogen fertilization raised the N content (in shoots and leaves) and maize yield (in the shoot dry matter and grain). The maize grown after soybean had both greater N concentrations and production (dry matter and grain) relative to the maize grown after maize. Applying 120 kg ha-1 N did not significantly affect the evaluated variables, regardless of the winter crop.
Nitrogen fertilization management in no-tillage maize with different winter crops
Keywords: Preplanting fertilization; Soybean; Split application of nitrogen; Tropical soil; Zea mays